Community-Police Relationships in Crime Reduction in the Tzaneen Area of the Limpopo Province (South Africa) - Tumiso D. Mokhomole; Adewale A. Olutola (UIN Sunan Gunung Djati, 2023)
This article explores the consequences of police-community relationships for crime reduction in the Tzaneen area of the Limpopo province of South Africa. This is relevant because even though the South African Police Service (SAPS) typically works under pressure and under difficult conditions of lack of resources and internal conflicts, the Tzaneen community still believes that it is the responsibility of the police to ensure a lower crime rate and a safer community. Presently, there are ineffective crime reduction programmes in the Tzaneen area, despite efforts such as ‘community policing forums’, ‘sector crime forums’, ‘take a Girl Child to Work’, and ‘Adopt a Cop’, which are practised in certain community areas in Tzaneen. Notwithstanding all these measures, the crime rate is high in the Tzaneen area. A qualitative interview method was used to collect data. Eighteen participants were interviewed from a selected panel of experts from the SAPS, community leaders, non-governmental organisations, and business communities by making use of open-ended questions. The study adopted purposive sampling. The study revealed several reasons for the high crime rate in the Tzaneen policing area, such as police corruption, lack of adequate communication between the police and the Tzaneen community, lack of community knowledge of the functions of the criminal justice system, and low morale on the part of policing organisations as some of the major reasons for the poor police-community relationship in the Tzaneen area of Limpopo. The study recommends ways that can strengthen the police-community relationship and reduce the crime rate in the Tzaneen area of Limpopo.